2005
DOI: 10.1523/jneurosci.5032-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cell-Specific Ablation of Laminin γ1 Causes Apoptosis and Prevents Proliferation

Abstract: To investigate the function of laminin in peripheral nerve development, we specifically disrupted the laminin ␥1 gene in Schwann cells. Disruption of laminin ␥1 gene expression resulted in depletion of all other laminin chains known to be expressed in Schwann cells. Schwann cells lacking laminin do not extend processes required for initiating axonal sorting and mediating axon-Schwann cell interaction. They fail to downregulate Oct-6 and arrest at the premyelinating stage. The impaired axon-Schwann cell interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
213
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(220 citation statements)
references
References 45 publications
3
213
0
4
Order By: Relevance
“…PI3-kinase activation in laminin-deficient Schwann cells is severely reduced (Yu et al, 2005), which may be a consequence of the impaired differentiation (Taveggia et al, 2005). However, disruption of laminins may also contribute to the reduction of this survival pathway, which results in apoptosis based on the following observations.…”
Section: Laminin Signaling In Schwann Cell Survivalmentioning
confidence: 95%
See 2 more Smart Citations
“…PI3-kinase activation in laminin-deficient Schwann cells is severely reduced (Yu et al, 2005), which may be a consequence of the impaired differentiation (Taveggia et al, 2005). However, disruption of laminins may also contribute to the reduction of this survival pathway, which results in apoptosis based on the following observations.…”
Section: Laminin Signaling In Schwann Cell Survivalmentioning
confidence: 95%
“…Mouse Schwann cells lacking the laminin g1 subunit lose all laminin expression, and mice carrying this mutation show a severe phenotype (Yu et al, 2005(Yu et al, , 2007. These mice exhibit tremor, muscle weakness, and hind limb paralysis, preventing most of them from reaching adulthood.…”
Section: Regulation Of Schwann Cell Function By Laminins and Laminin mentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, while proliferation is high in Schwann cell precursors, the maximum rate of division occurs in immature Schwann cells at E18/19 (Stewart et al, 1993). Similarly, in mice, proliferation is high at the Schwann cell precursor stage (E13), but significantly increases and reaches a peak at the immature Schwann cell stage (E15 onwards) (Yu et al, 2005). Schwann cell proliferation has been shown to be axonally induced in in vitro studies, where direct contact with neurites and neurite fractions were shown to induce cell division in Schwann cells (Salzer et al, 1980).…”
Section: Control Of Immature Schwann Cell Numbersmentioning
confidence: 99%
“…An evolving but incomplete model holds that laminin (or basement membrane) ligation of b1 integrins promotes lammellipodial extension and axonal interdigitation through alterations of the activated state of Rac1, Cdc42 and Rho/ Rho kinase. Laminins can affect both Schwann cell proliferation and process extension and proliferation whereas b1-integrins affect only the former (Yu et al 2005;Yu et al 2009). …”
Section: Peripheral Nerve Axonal Envelopment and Myelinationmentioning
confidence: 99%